2020
DOI: 10.1039/d0qo00559b
|View full text |Cite
|
Sign up to set email alerts
|

An enzymatic acetal/hemiacetal conversion for the physiological temperature activation of the alkoxyamine C–ON bond homolysis

Abstract: Enzymatic trigger. Upon enzymatic hydrolysis by Subtilisin A, highly stable alkoxyamines are transformed into highly labile alkoxyamines able to homolyze spontaneously in less than 500 seconds, at 37 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Chemical, [88][89][90] biological, [91,92] or plasmonic [93,94] stimuli are relatively new as triggers for dynamic alkoxyamine bond dissociation. Although these stimuli have not been exploited in alkoxyamine-based CANs, they were already successfully utilized in NMP or as smart alkoxyamines.…”
Section: Other Stimulimentioning
confidence: 99%
“…Chemical, [88][89][90] biological, [91,92] or plasmonic [93,94] stimuli are relatively new as triggers for dynamic alkoxyamine bond dissociation. Although these stimuli have not been exploited in alkoxyamine-based CANs, they were already successfully utilized in NMP or as smart alkoxyamines.…”
Section: Other Stimulimentioning
confidence: 99%
“…Kinetics of 22 (●) and 24 (■) in the absence (red) and presence (blue) of subtilisin A (1.5 mM) in buffer (pH 7.4) solution at 37 °C. Adapted with permission from ref . Copyright 2020 Royal Society of Chemistry.…”
Section: Tools For Smart Applicationsmentioning
confidence: 99%
“…Interestingly, at 37 °C, in the presence of subtilisin A, 64 mixed acetal 22 and 24 are hydrolyzed into their corresponding aldehydes 23 and 25, affording t max values of 1500 and 500 s, respectively (Figure 23), whereas t 1/2 values of 42 million years and 330 years are expected in the absence of enzymatic activation (Scheme 3). 1 Such a large switch is due to the combination of polar, stabilization, steric, and solvent effects.…”
Section: Smart Alkoxyamines As Theranostic Agents For the Treatment O...mentioning
confidence: 99%
“…In the last decade, the concept of smart alkoxyamines has been developed. 1 These are highly stable alkoxyamines with half-lives of several hundred years, which can be selectively transformed into highly labile species with half-lives of seconds or minutes through chemical, 2-5 photochemical [6][7][8][9] or biochemical 10,11 events. Such alkoxyamines have interesting properties for potential applications in industry, e.g., safe storage of initiators for radical polymerizations, 5,12 or in biology, e.g., drugs for cancer or parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Such alkoxyamines have interesting properties for potential applications in industry, e.g., safe storage of initiators for radical polymerizations, 5,12 or in biology, e.g., drugs for cancer or parasites. 10,11,[13][14][15][16][17][18] While the focus of these studies has been on triggering alkoxyamine homolysis, to form a nitroxide and carbon-centred radical, recently it has been shown that upon oxidation, through electrochemical [19][20][21][22][23] or photoredox 24,25 methods, alkoxyamines can spontaneously undergo mesolytic cleavage instead. Depending on the leaving group and other species present, this process can yield nitroxides and carbocations, or alternatively oxoamoniums and carbon-centred radicals.…”
Section: Introductionmentioning
confidence: 99%